2014
DOI: 10.1093/aob/mcu053
|View full text |Cite
|
Sign up to set email alerts
|

Pectic-β(1,4)-galactan, extensin and arabinogalactan–protein epitopes differentiate ripening stages in wine and table grape cell walls

Abstract: Combinations of cell wall probes are able to define distinct ripening phases in grapes. Pectic-β-(1,4)-galactan epitopes decreased in abundance from green stage to véraison berries. From véraison there was an increase in abundance of significant extensin and AGP epitopes, which correlates with cell expansion events. This study provides new ripening biomarkers and changes that can be placed in the context of grape berry development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
56
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(61 citation statements)
references
References 105 publications
5
56
0
Order By: Relevance
“…For example, this technique has been applied to determine changes in cell wall polysaccharide distributions during plant development. [6,7] The frequently used rat monoclonal antibody LM5 is known to bind β-1,4-linked galactans. [8] LM5 has been applied in immunohistochemical analysis, immunofluorescence microscopy, live cell labeling and for glycan microarray screening.…”
Section: Introductionmentioning
confidence: 99%
“…For example, this technique has been applied to determine changes in cell wall polysaccharide distributions during plant development. [6,7] The frequently used rat monoclonal antibody LM5 is known to bind β-1,4-linked galactans. [8] LM5 has been applied in immunohistochemical analysis, immunofluorescence microscopy, live cell labeling and for glycan microarray screening.…”
Section: Introductionmentioning
confidence: 99%
“…Aroma is one of the major factors that determine the quality of the wine, showing the skins more than a half of the volatile compounds present in the grape berries [19]. It is well known that the grape berry skin cell walls consist of cellulose, hemicellulose, and are particularly rich in pectin [13,25]. This pectin component contains a number of polymers HG, RG-I, side chains such as arabinans and galactans, RG-II and AGP [25,26], and was proposed to be associated with other cell wall polymers (cellulose and hemicellulose) [27].…”
Section: Grape Polysaccharides: Origin Structure and Functionsmentioning
confidence: 99%
“…Grape berry ripening consists of a cell division (green) phase followed by a cell expansion (ripe) phase [25]. The onset of this second phase known as veraison is marked by the initiation of events such as sugar accumulation, a decrease in organic acids, color development, berry expansion and fruit softening.…”
Section: Grape Polysaccharides: Origin Structure and Functionsmentioning
confidence: 99%
“…CoMPP has been used to analyze the composition of polysaccharides extracted from model organisms such as Arabidopsis thaliana and Physcomitrella patens (65). Applications of potential commercial interest include the tracking of polysaccharide fates during grape ripening and fermentation (147,148). Investigations into the stability of noncellulose compounds during textile processing of cotton fiber showed that Arabinoxylan: major polysaccharide component of plant cell walls some polysaccharides are largely unaffected and might be used for functionalization procedures for the final cotton product (149).…”
Section: Plant Polymer Profilingmentioning
confidence: 99%